Fundamental parameters of the LMC clusters NGC 1836, NGC 1860, NGC 1865, SL 444, LW 224 and SL 548 - Piatti, Andres Eduardo (2003)
Complementing our recent Washington photometric studies on intermediate age and young Large Magellanic Cloud (LMC) clusters, we now turn our attention to six previously unstudied star clusters in the transition range 200-700 Myr. We study NGC 1836, NGC 1860 and NGC 1865, which are projected on the LMC bar; SL 444, also located in the central disc but outside the bar; and LW 224 and SL 248, both located in the outer disc. We derive ages and metallicities from extracted T_1 versus C-T_1 colour-magnitude diagrams (CMDs), using theoretical isochrones recently computed for the Washington photometric system. For the metallicity determinations, these CMDs are particularly sensitive. We also estimate ages and metallicities of the surrounding fields of NGC 1860 and 1865 by employing the deltaT_1  index defined in Geisler et al. (1997, AJ, 114, 1920) and theoretical isochrones. By adding the present cluster sample to those of our previous studies, we now gather 37 LMC clusters with homogeneous parameter determinations, which are employed to probe the chemical enrichment of the LMC and its spatial distribution. On average, inner disc clusters turned out to be not only younger than the outer ones, but also more metal-rich; some have solar metal content. Furthermore, inner clusters located to the west of the LMC centre are younger and more metal-rich than their eastern counterparts. We propose that a bursting formation mechanism, with an important formation event centred at approximately 2 Gyr, provides a better description of the cluster age-metallicity relation than a closed-box chemical evolution model. In the outer disc, the field star formation seems to have lasted until 2 Gyr ago while it continued in the inner disc for almost 1 Gyr longer.